1980
DOI: 10.1007/bf00114339
|View full text |Cite
|
Sign up to set email alerts
|

Charge imbalance waves and nonequilibrium dynamics near a superconducting phase-slip center

Abstract: Using a generalized two-fluid picture to describe a quasi-one-dimensional superconductor near To we provide a heuristic derivation for a set of equations governing the temporal and spatial evolution of the charge imbalance (or branch imbalance) in the quasiparticles. We show that these equations are isomorphic to those that describe a simple electrical transmission line, so that charge imbalance waves may propagate in the superconductor in analogy with electrical signals that propagate down the transmission li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Note that RQ* is in series with, and independent of, the familiar tunnel oxide resistance, which we call R 0 x for clarity. 6 , and this is the first supporting experimental evidence. …”
Section: By Using Eq (1) We Findsupporting
confidence: 67%
“…Note that RQ* is in series with, and independent of, the familiar tunnel oxide resistance, which we call R 0 x for clarity. 6 , and this is the first supporting experimental evidence. …”
Section: By Using Eq (1) We Findsupporting
confidence: 67%
“…This could thus be another explanation for the similarity of the critical currents of the bridges near the crossover. Based on theory, phase slippage in the structure results in both intrinsic 27 and thermal hysteresis 28,29 in the IV characteristics of a superconducting nanobridge. In practice, this means that, in order to obtain electronic components with nonhysteretic IV characteristics, the nature of the CPR should be single valued.…”
Section: Resultsmentioning
confidence: 99%
“…Refinements of the SBT model have been proposed by Kadin et al, 26 by Ivlev and Kopnin 27,28 and by Baratoff. 29 Kadin et al have found that propagating waves of charge imbalance can be excited at the PSC and identified an intrinsic mechanism of hysteresis in the V(I) characteristics.…”
Section: Modelsmentioning
confidence: 99%